The Mediating Effect of Corporate Communication on Image of Organization and Reputation of Organization: (A Case Study of Scancom Ghana Limited - MTN) - Osew, Nana Odei Raphael (UniMAC - GIJ, 2015)
The purpose of this research was to examine the mediating effect of corporate communication on image of organization and reputation of organization using MTN as the case study. Primary data was collected from customers of MTN at five (5) different sales centre of the network through a survey of one hundred (100) questionnaires. The research adopted a quantitative research method in conducting the study; a five-point likert scale questionnaire was developed to collect data for the study using simple random sampIing method. A Statistical Package for Social Studies (SPSS) software was used for easy and accurate computation of quantitative survey results and a multiple regression analysis was tested to know the extent to which the independent variable (corporate communication) accounted for a variation in the dependent variables (image of organization and reputation of organization). At the end of the analysis, the results from the data showed a positive level of correlation of the variables that were tested. It was found out that the results from the analysis support the hypothesis that was put forward for testing, it was also found out that corporate communication is the best predictor of reputation of organization and corporate communication is directly linked to reputation of organization and all the variables entered for reputation are interdependent as shown in the results from the analysis.
Thesis